ESTIMATING THE ACTUAL DIET AND FOOD STATUS OF OBSESS MEN - Guli I. Shaykhova; D.Kh. Ibrokhimova; Sh.A. Zokirkhonova; D.A. Ataxanova; M.O. Zaydullaeva (Central Asian Journal of Medicine, 2022)
Obesity is a chronic relapsing disease, today it is one of the most widespread non-communicable diseases: in 1998, there were 250 million obese patients in the world, and by 2025, according to WHO experts, their number will exceed 300 million. The aim of this work was to study the actual nutrition and nutritional status, as well as physical activity of obese men. Materials and methods. The study involved 250 men aged 40 to 55 years old, diagnosed with obesity of 1-11 and 111 degrees, living in the city of Tashkent and the Tashkent region. 30 men made up the control group. The study was carried out at the Levelmed clinic in Tashkent. Results and discussion: The diet of obese men is characterized by quantitative and qualitative deficiencies: body mass index, waist and hip circumference are above normal. Violated the diet in the form of irregular food intake, food at the late hours of the day, massive consumption of high-calorie foods: saturated animal fats, salt and sugar.